2008
DOI: 10.1111/j.1601-5223.1982.tb00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute myelogenous leukemia in a child with primary involvement of chromosomes 11 and X

Abstract: The chromosomes of a case of acute myelogenous leukemia in an infant of 7 months were analyzed by means of high resolution banding achieved without mitotic synchronization. The analyses were based on 2 cell samples taken, (1) at diagnosis before treatment, and (2) 3 months later during partial remission, before the onset of the terminal phase. All cells of both samples contained 2 deviating chromosomes resulting from rearrangements of X at q22 and of 11 at p13, p15 and q23. Twenty‐seven per cent of the cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…34 MLL fusion partners are very diverse and the leukemogenic program developed is influenced by the identity of the fusion partner, as well as by microenvironmental signals. 35,36 MLL-AFX1 is a rare translocation observed in both human AML [37][38][39][40] and T-ALL 41,42 ; in fact, it has been suggested that happens early in hematopoietic cells before commitment to distinct lineages. 41 MLL-AFX1-expressing NSG-engrafting AMLs produce a myeloid leukemia in humans, but induce a T-lymphoproliferative disorder in NOD/SCID IL2R␥c null mice, which could be explained based on the inability of human cells to recognize mouse myeloid factors, and by the existence of putative lymphoid signals in the NOD/SCID IL2R␥c null BM microenvironment that NOD/SCID and NOD/SCID ␤2 Ϫ/Ϫ mice may lack.…”
Section: Discussionmentioning
confidence: 99%
“…34 MLL fusion partners are very diverse and the leukemogenic program developed is influenced by the identity of the fusion partner, as well as by microenvironmental signals. 35,36 MLL-AFX1 is a rare translocation observed in both human AML [37][38][39][40] and T-ALL 41,42 ; in fact, it has been suggested that happens early in hematopoietic cells before commitment to distinct lineages. 41 MLL-AFX1-expressing NSG-engrafting AMLs produce a myeloid leukemia in humans, but induce a T-lymphoproliferative disorder in NOD/SCID IL2R␥c null mice, which could be explained based on the inability of human cells to recognize mouse myeloid factors, and by the existence of putative lymphoid signals in the NOD/SCID IL2R␥c null BM microenvironment that NOD/SCID and NOD/SCID ␤2 Ϫ/Ϫ mice may lack.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral leucocytes at diagnosis of this ALL case were cultured and are presently known as the KARPAS-45 cell line (Karpas et al, 1977). In addition, MLL/AFX1 fusion was confirmed in an AML case with highly complex change originally published involving the Xq22 locus (Nacheva et al, 1982;Parry et al, 1994;Borkhardtet al, 1997). Note This translocation has also been found in 2 cases of CLL (Bentz et al, 1995;Kalla et al, 2005).…”
Section: Diseasementioning
confidence: 89%
“…Schoch et al, 2003;Palandri et al, 2009;Fabarius et al, 2011;Sun et al, 2011) and 1 AML (de Souza et al, 2000). t(15;17)(q24;q21) was found in 2 cases (Berger et al, 1988;Cuneo et al, 1992), 21q22 abnormalities in 5 (Raimondi et al, 1999;Kim et al, 2009;Jekarl et al, 2010) and 11q23 rearrangements in 4 AML patients (Nacheva et al, 1982;Harrison et al, 1998;Taylor et al, 2000;Clavio et al, 2001 ). Cytogenetic clonal variation with karyotypically unrelated clones was found in 5 MPN (RegeCambrin et al, 1987;Andrieux et al, 2003;Alfaro et al, 2008;Hild and Fonatsch 1990;Sun et al, 2011) and 2 AML patients (Alter et al, 2000;Strehl et al, 2001).…”
Section: Additional Anomaliesmentioning
confidence: 99%